2007
DOI: 10.3115/1599600.1599734
|View full text |Cite
|
Sign up to set email alerts
|

Small-group face-to-face discussions in the classroom

Abstract: This paper presents a relatively new direction of CSCL research: small-group learning in the classroom. This research direction has received relatively little attention within the CSCL community. In this paper we explore the possibilities of collaborative technology in the classroom. We use the distinction between task-related and social-emotional interactions as a criterion for computer support. It is hypothesized that the students will use the collaborative technology purely for task-related interactions whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…When students collaborate they have to maintain durable relationships and acceptable levels of participation. Interactions that are associated with these aspects of the group performance can be typified as social-emotional interactions [70]. These interactions are primarily directed towards the relationship between group members [12].…”
Section: Emotions In Educationmentioning
confidence: 99%
“…When students collaborate they have to maintain durable relationships and acceptable levels of participation. Interactions that are associated with these aspects of the group performance can be typified as social-emotional interactions [70]. These interactions are primarily directed towards the relationship between group members [12].…”
Section: Emotions In Educationmentioning
confidence: 99%
“…Small groups supported by technology in undertaking collaborative learning in the classroom have received relatively little attention in the HCI research community [ 5,3]. The work of Dillenbourg et al [ 7,8] on orchestration identified this gap where in [ 8] they defined orchestration as "the real time management by a teacher of multiple learning activities within a multi-constrained environment".…”
Section: Orchestrationmentioning
confidence: 99%
“…Several initiatives have been implemented in CSCL for the classroom and some examples of these experiences are described by Zurita and Nussbaum (2004) and Diggelen and Overdijk (2007) who performed small group collaborations; Hung et al (2009) who developed a collaborative English vocabulary-acquisition-game system; and Zea et al (2009) who made a collaborative video-game to teach vowels. In these cases, the research focused on small groups, where each participant had his own device.…”
mentioning
confidence: 98%